Soil Physical-chemical Traits and Soil Quality Index in a Tropical Cambisol as Influenced by Land Uses and Soil Depth at Apodi Plateau, Northeastern Brazil - Gondim, Joaquim Emanuel Fernandes; Souza, Tancredo; Portela, Jeane Cruz; Santos, Djail; Nascimento, Gislaine dos Santos; da Silva, Lucas Jonatan Rodrigues [UNESP] (Springer Nature, 2023)
The soil physical-chemical changes in different land uses in a Tropical Cambisol at Apodi Plateau, Northeastern Brazil, were investigated between May 2017 and April 2018. Soil samples were collected at three soil layers (0–5, 5–15, and 15–25 cm) under three land uses: a 6-year agroecological farming system, a 10-year fruticulture farming system, and a 6-year conventional farming system. We evaluated: bulk density, soil porosity, weighted average diameter (WAD), geometric mean diameter (GMD), soil pH, soil organic carbon (SOC), P, and sum of bases. Soil quality index was built by considering four main functions: Water supply and storage, root growth capacity, nutrient cycling, and soil conservation. Our results emphasized the land use influence on the soil physical-chemical traits in a Tropical Cambisol. The PCA analyses showed that SOC, soil porosity, bulk density, WAD, GMD, soil pH, sum of bases, and soil P content were the main factors contributing to the data variance. We found the highest values of soil quality index in the conventional farming system (0.57 ± 0.03). The results highlight the importance to consider land uses that increase the sum of bases, WAD, GMD, and SOC content, and decrease bulk density. Our findings suggest that (1) a conventional farming system with liming and fertilizers’ input positively changed soil physical-chemical traits, which in turn improved soil quality in a tropical Cambisol; and (2) by altering soil functions land uses may create a sustainable cycle into the soil profile thus promoting soil quality.
Keywords: Agroecological farming system; Caatinga; Conventional farming system; Fruticulture farming system; Nutrient cycling; Soil conservation